ANALYSIS OF CODE MIXING IN THE FIRST EPISODE OF THE SERIES PRIVATE BODYGUARD (2024) - Nasywa Kamila, Lathifah; Setiawan Djuharie, Otong; Priyawan, Pepen (Universitas Putera Batam, 2025)
This study analyzes code mixing patterns and functions in the first episode of the 2024 series Private Bodyguard. Code mixing, a notable sociolinguistic phenomenon, involves speakers switching between languages in conversation. The research aims to understand language dynamics in a broader social context and the role of code mixing in contemporary media. Employing a qualitative approach, data was collected from dialogues in the series via the Viu streaming platform. The study categorizes code mixing based on Muysken's typology: insertion, alternation, and congruent lexicalization. The analysis found eighteen instances of code mixing. Insertion was the most common type (8 examples), reflecting English's influence on young Indonesians exposed to global culture. Alternation occurred seven times, proving comfortable bilingual switching to emphasize or express emotions. Congruent lexicalization (3 examples) showed seamless integration of words with similar grammatical structures. This study highlights the dynamic interaction between language, culture, and society in Indonesia.